A Study on the use of Social Media as a Tool of Citizen Journalism with Special Reference to the Updates on Kerala Flood Relief - P, Sathya (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Social networking is a unique platform for content sharing used by people all over the world irrespective of vast differences in language, culture and societal norms. The connectivity, flexibility and ease of access have lead to the utilization of these social networks as a tool of citizen journalism. Now-a-days, people exhibit their social responsibility by informing or reporting about the problems in the society through these social networks that reaches the masses which in turn makes press and media, government officials and authorities to look into the issue. Kerala, famously called as “The God’s own Country” is facing its worst time ever with the pouring rainfall, flooding rivers, landslides and people are losing their lives, getting displaced and are being accommodated in several camps in the state. In this situation, people in and around Kerala is using social media to organise, collect, and distribute the relief funds and materials required in different locations. It is noted that immediate requirements are informed to people through social media and it is being fulfilled at the earliest. The purpose of this study is to explore the utilization of social networks as the journalistic tool by the citizens and attempt to sooth the hardships faced by the people. How to cite this article: Sathya P. A Study on the use of Social Media as a Tool of Citizen Journalism with Special Reference to the Updates on Kerala Flood Relief. J Adv Res Jour Mass Comm 2018; 5(4): 50-53. DOI: https://doi.org/10.24321/2395.3810.201819